Biological Properties of Staphylococcal Enterotoxin-Like Toxin Type R - Omoe, Katsuhiko (American Society for Microbiology, 2004)
We investigated the biological properties of a novel staphylococcal enterotoxin-like putative toxin, staphylococcal enterotoxin-like toxin type R (SElR). Major histocompatibility complex class II molecules were required for T-cell stimulation by SElR. SElR stimulated T cells bearing receptors Vβ 3, 11, 12, 13.2, and 14. These results suggested that SElR acts as a superantigen.